Environmental sustainability of production. Economic performance and potential production on farms belonging to within regions of Wielkopolski I Śląska in 2004-2010 - Smędzik-Ambroży, Katarzyna (Progress in Economic Sciences; No 1 (2014): Progress in Economic SciencesDO - 10.14595/PIES/01/004)
The objective of the study was to evaluate the economic results and production potential of FADN farms in the Wielkopolska and Śląsk regions, which realize varying amount of criteria for theenvironmental sustainability of agricultural production in the years 2004-2010. As a result of the analysis the following hypothesis is confirmed: farms from the Wielkopolska and Śląsk regions, which  so not realize the criteria of environmental sustainability of agricultural production reached, in 2004-2010, higher economic results than farms, which realize all of the criteria of environmental sustainability of agricultural production. In each of the years of the study period in the group of farms which not realize the criteria of environmental sustainability of agricultural production reached higher values of total income from agricultural production, as well as higher indicators of the effectiveness of land and labour inputs. With the exception of 2007 and 2010 higher absolute values of agricultural profits were reached in these farms too. At the same time the farms which permanently not realize the criteria were characterized lower inputs of land and labour as well as a higher intensity of livestock production.